Love and marital satisfaction among urban Malays: comparing three groups length of marriage - Suzana Mohd Hoesni,; Norba’yah Abdul Kadir,; Wan Shahrazad Wan Sulaiman,; Sarah Waheeda Muhammad Hafidz, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Love is an important psychological entity in relation to marital satisfaction. Therefore, this study aimed to compare how married couples from three groups’ length of marriage (1-5 years, 6-18 years and 19 years) perceive love (intimacy, passion and commitment) and to compare marital satisfaction across three length of marriage. This study applied the survey research design using a combination of cluster and stratified sampling techniques. Questionnaires which were distributed consisted of ques-tions related to personal background, marital background, love and marital satisfaction. Malay mar-ried individuals residing in Lembah Klang from eight different locations who volunteered to partici-pate in this study were given questionnaires to complete. 310 participants (155 males and 155 fe-males) completed the questionnaires which later were collected for data analysis. Results showed that there were significant differences on how three groups length of marriage (1-5 years, 6-18 years and 19 years above of marriage) perceive love (commitment and passion). However, there were no differ-ences in marital satisfaction between the three groups length of marriage as suggested by previous research. Results indicated that love has an important psychological role at any stages of marriage. This research suggested that more research should explore the psychological aspects of love within marriage and its contribution to psychological wellbeing of married couples.